Defining a Patient-Centred Core Outcome Domain Set for the Assessment of Hearing Rehabilitation With Clients and Professionals - Allen, David; Hickson, Louise; Ferguson, Melanie (Frontiers in Neuroscience, 2022)
Background A variety of outcome domains are currently measured for the assessment of hearing rehabilitation. To date, there is no consensus about which outcome domains should be measured, when they should be measured, and how they should be measured. In addition, most studies seeking to develop core outcome sets and measures for hearing rehabilitation services have primarily focussed on the opinions and expertise of researchers, and, to a lesser extent, clinicians, rather than also involving clients of those services. The principles of experience-based co-design suggest that health services, researchers, and policymakers should come together with clients and their families to design health services and define what metrics should be used for their success. Objectives This study aimed to seek views and consensus from a range of key stakeholders to define which client-centred self-report outcome domains should be measured, when they should be measured, and how they should be measured, in a national publicly funded hearing rehabilitation scheme. In addition, the study aimed to identify current and future potential mechanisms and systems to standardise the collection of data and reporting of outcomes, to enable comparison across clients and hearing service providers. Methods Two stakeholder groups participated in a three-round online Delphi process: (1) 79 professional stakeholders involved in the delivery of hearing services in Australia, and (2) 64 hearing rehabilitation services’ clients identified by not-for-profit consumer organisations. An initial set of in-person workshops scoped the key issues upon which to develop the initial open-ended questions and subsequent Likert-scale statements addressing these issues. These statements were then distributed to both groups in an online survey. The respondent ratings were summarised, and the summary was returned to respondents along with a second round of the survey. This process was then repeated once more. The five most important outcome domains from both groups were then combined, and a consensus workshop of seven professionals and three client advocates agreed on the top four ranked domains. Results A range of potential outcome domains were identified as relevant indicators of successful hearing rehabilitation. Communication ability, personal relationships, wellbeing, and participation restrictions were identified as a core outcome domain set that should be measured as a minimum for patients receiving hearing rehabilitation. There was little agreement on the preferred timepoints for collection of outcome measures, with respondents expressing the view that this should be established by research once a set of outcome measures has been selected. However, there was broad agreement that measurements of these domains should be collected at baseline (before the provision of hearing rehabilitation) and no earlier than 3 months following the completion of rehabilitation. Potential benefits and issues with the development of a national outcomes database/collection system were also identified and prioritised, with participants highlighting the importance of valid, high-quality, trustworthy, and comprehensive data collection. Conclusion These results provide a Core Outcome Domain Set for the self-reported evaluation of hearing rehabilitation and provide important background information for the design of methods to implement them across hearing healthcare systems. However, the wide range of outcome domains identified as potentially providing important additional information and the lack of specific measures to address these domains strongly suggest that there is still more research to be done. Ongoing stakeholder engagement will continue to be vital for future implementation. In addition, further research is required to determine the optimal time following hearing rehabilitation to utilise any particular outcome measure.